Sponges of the family Axinellidae (Porifera: Demospongiae) in Indonesia - Alvarez, Belinda; Voogd, Nicole J. De; Soest, Rob W.m Van (Zootaxa, 2016)
Nine species in five genera of the family Axinellidae, including three new species, Axinella badungensis sp. nov., A. balinensis sp. nov. and Phycopsis pesgalli sp. nov. are recorded from Indonesian waters within the limits of the Western Coral Triangle province. Descriptions and discussion of those species are presented here. Four new combinations, Phakettia arbora (Sim, Kim & Byeon, 1990) comb.nov., P. trachys (De Laubenfels, 1954) comb.nov., Echinoclathria retepora (Lendenfeld, 1887) comb.nov. and Amphimedon hispidula (Ridley, 1884) comb.nov. are also established here. The distributions of species previously described are here extended to the study area with the exception of Phakellia atypica which seems so far restricted to Indonesia.